Green synthesis of Au decorated CoFe2O4 nanoparticles for catalytic reduction of 4-nitrophenol and dimethylphenylsilane oxidation. Issue 38 (16th July 2019) - Saire-Saire, Samuel; Barbosa, Eduardo C. M.; Garcia, Daniel; Andrade, Leandro H.; Garcia-Segura, Sergi; Camargo, Pedro H. C.; Alarcon, Hugo
Abstract : We present a cleaner chemical synthesis process of a magnetic recoverable Au/CoFe2 O4 hybrid nanocomposite catalyst that has remarkable activity in catalytic reduction and oxidation, improved by surface plasmon resonance. Abstract : Gold nanoparticles (Au NPs) have been widely employed in catalysis. Here, we report on the synthesis and catalytic evaluation of a hybrid material composed of Au NPs deposited at the surface of magnetic cobalt ferrite (CoFe2 O4 ). Our reported approach enabled the synthesis of well-defined Au/CoFe2 O4 NPs. The Au NPs were uniformly deposited at the surface of the support, displayed spherical shape, and were monodisperse in size. Their catalytic performance was investigated towards the reduction of 4-nitrophenol and the selective oxidation of dimethylphenylsilane to dimethylphenylsilanol. The material was active towards both transformations. In addition, the LSPR excitation in Au NPs could be employed to enhance the catalytic performance, which was demonstrated in the 4-nitrophenol reduction. Finally, the magnetic support allowed for the easy recovery and reuse of the Au/CoFe2 O4 NPs. In this case, our data showed that no significant loss of performance took place even after 10 reaction cycles in the oxidation of dimethylphenylsilane to dimethylphenylsilanol. Overall, our results indicate that Au/CoFe2 O4 are interesting systems for catalytic applications merging high performances, recovery and re-use, and enhancement of activities under solar light illumination.